Additional ORFs in Plant LTR-Retrotransposons - Vicient, Carlos M.; Casacuberta, Josep M. (Frontiers in Plant Science, 2020)
LTR-Retrotransposons share a common genomic organization in which the 5′ long terminal repeat (LTR) is followed by the gag and pol genes, and terminates with the 3′ LTR. Although GAG-POL-encoded proteins are considered sufficient to accomplish the LTR-retrotransposon transposition, a number of elements carrying additional open reading frames (aORF) have been described. In some cases the presence of an aORFs can be explained by a phenomenon similar to retrovirus gene transduction, but in these cases the aORFs are present in only one or a few copies. On the contrary, many elements contain aORFs, or derivatives, in all, or most, of their copies. These aORFs are more frequently located between pol and 3’LTR, and they could be in sense or antisense orientation respect to gag-pol. Sense aORFs include those encoding for ENV-like proteins, so called because they have some structural and functional similarities with retroviral ENV proteins. Antisense aORF between pol and 3’LTR are also relatively frequent and, for example, are present in some characterized LTR-retrotransposon families like maize Grande, rice RIRE2 or Silene Retand, although their possible roles have been not yet determined. Here, we discuss the current knowledge about these sense and antisense aORFs in plant LTR-retrotransposons, suggesting their possible origins, evolutionary relevance and function.